Association between symptoms of covid-19 infection and adverse maternal-perinatal outcomes in pregnant women at a referral hospital - Angulo-Fernandez, Kevyn (2023)
Objectives. To determine the association between symptoms of COVID-19 infection and adverse maternal-perinatal outcomes in pregnant women from a referral hospital. Materials and methods. Analytical cross-sectional study of women in the third trimester of pregnancy hospitalized due to COVID-19 in the gynecology and obstetrics area of a general hospital in Lima during 2020. Clinical and obstetric variables were collected. Fisher’s exact test and Chi-square test were used during the descriptive analysis. Poisson regression was used to find the association between the variables of interest, with a 95% confidence interval (95%CI). Results. A total of 272 pregnant women were included, 50.3% of whom had symptoms of infection. Of these, 35.7% of the pregnant women and 16.5% of the newborns had an adverse outcome. Having symptoms of COVID-19 infection increased the risk of maternal complications as a whole (PR= 2.32 95%CI: 1.61-3.34), premature rupture of membranes (PR= 2.73 95%CI: 1.51-4.94) and preeclampsia (PR= 2.73 95%CI: 1.51-4.94). Similarly, symptoms of COVID-19 infection increased the risk of perinatal complications as a whole (PR= 2.51 95%CI: 1.34-4.68) and acute fetal distress (PR= 2.99 95%CI: 1.07-8.38)]. Conclusions. The presence of symptoms of COVID-19 infection increase the risk of adverse maternal-perinatal outcomes